Penerapan Teknologi Biopori Di Perumahan Griya Tabing Banda Gadang Padang Muara - Mulya Gusman; Yoszi Mingsi Anaperta; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. Problems of environmental damage such as flood, garbage and drought in Indonesia is a problem that can not be solved. One of the things that cause problems to this flood is this is the decreasing of water absorption area and unconscious society not to throw garbage carelessly. Limited land in residential areas results in space for water catchment areas and few dumps. The purpose of this community service activity is to provide knowledge and skills to the community about the application of environmentally appropriate technology that is Biopori Absorption Hole technology (LRB). This activity is useful to increase the ground water reserves and reduce the waste as well as to produce compost. Partners of this activity are 2 groups of residents Rukun Tetangga (RT) that is RT 04 and RT 06 Village Tabing Banda Gadang, District Nanggalo, Padang. This form of activity consists of lectures and practices of making biopore infiltration holes. The practice of making the biopore infiltration hole involves community participation. Many of the created biopore holes are made up of 10 holes per each RT. The hole is 10 cm in diameter and 100 cm in depth. The holes that have been made therein incorporated organic waste in the form of remnants of vegetables, paper, fruit peels and others - others. Thus LRB is useful in reducing waste, increasing groundwater reserves, reducing the flow of surface water that causes flooding and will reduce the dangers of drought. Besides, LRB will produce compost that can be useful to increase people's income. Keywords: Biopori Absorption Hole (LBR), Flood, Organic and Inorganic Waste.